Emergency Physician Training on Mild Traumatic Brain Injury: A Systematic Review. Issue 4 (15th September 2017) - Patrick, Sean P.; Gaudet, Lindsay A.; Krebs, Lynette D.; Chambers, Thane; Rowe, Brian H.
Abstract: Objectives: Mild traumatic brain injury (mTBI) is the most common emergency department (ED) brain injury presentation worldwide. Despite its frequency, practice variation and care gaps exist among emergency physicians (EPs) in diagnosing and appropriately managing mTBI in the ED. The objective of this review was to identify mTBI‐specific training undertaken to improve the detection and management of mTBIs by EPs and its impact on practice. Methods: A comprehensive search strategy utilized four bibliographic databases, the gray literature and the keywords concussion, mild traumatic brain injury, medical education, and continuing medical education (CME). To be included, studies were required to report on mTBI training received by practicing EPs at any point during their medical education or career. Studies examining clinical practice guidelines or use of diagnostic tools without active implementation or formal training were not included. Two reviewers screened unique citations for relevance and reviewed the full texts of relevant articles. Two independent researchers extracted data and assessed methodologic quality. At all stages, a third independent reviewer adjudicated discrepancies. Results: Overall, five studies were included from 409 unique results. None of the included studies were of high quality. Identified training on mTBI consisted of three training toolkits, conference presentations and academic journal articles, and pediatric fellowship training. Training primarily occurred as CME and focused on awareness of and management of mTBI; three studies reported physician practice changes, including increases in the use of evidence‐based return‐to‐school and return‐to‐activity recommendations. Conclusions: The few studies identified addressing mTBI training targeting EPs demonstrate the limited attention given to this issue. The current evidence‐to‐practice gap in mTBI management places patients at risk for suboptimal care in the ED, and existing mTBI knowledge translation, including education, requires optimization to effectively address the current gap in evidence‐based practice for mTBI diagnosis and management in the ED.